2014
DOI: 10.1007/s00701-014-2130-9
|View full text |Cite
|
Sign up to set email alerts
|

No exacerbation of perihematomal edema with intraclot urokinase in patients with spontaneous intracerebral hemorrhage

Abstract: Hematoma evacuation using MIS leads to a significant reduction in PHE. Furthermore, the use of urokinase does not exacerbate PHE, making its hypothesized proedematous effects unlikely when the thrombolytic is administered directly into the clot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Furthermore, an increasing number of clinical studies have proposed that uPA carries a high fibrinolytic potential without excitotoxicity, thus representing a novel, promising candidate for fibrinolytic therapy for ICH. 5,8,23,38 In agreement with the above publications, our results also revealed the greater efficacy of uPA, compared with tPA, in ameliorating PHE and motor function after ICH.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, an increasing number of clinical studies have proposed that uPA carries a high fibrinolytic potential without excitotoxicity, thus representing a novel, promising candidate for fibrinolytic therapy for ICH. 5,8,23,38 In agreement with the above publications, our results also revealed the greater efficacy of uPA, compared with tPA, in ameliorating PHE and motor function after ICH.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, according to the proportion between hematoma size and drug dosage, the established dose of tPA and uPA are equivalent to the dosage in ICH patients. 8,23,26 To avoid additional injury to the normal perihematomal brain tissue during intraclot drainage, we used fibrinolytic injection alone rather than fibrinolytic injection with intraclot drainage. The bur hole was sealed with bone wax, and the skin incision was closed with sutures after the needle was removed.…”
Section: Experimental Groups and Fibrinolytic Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…So far, tPA is the most widely used fibrinolytic agent for IVH and ICH ( 33 ). However, increased evidence indicated that uPA was able to increase the rate of clot lysis without exacerbation of PHE, and improve outcomes in patients with spontaneous ICH ( 34 , 35 ). Notably, Gaberel et al demonstrated that, in contrast to tPA, uPA displayed a safer profile for intraventricular fibrinolysis following IVH regarding secondary inflammatory processes and neurotoxicity, as well as better neurological outcome in experimental models of IVH ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in recent years, UK, an older thrombolytic drug, has re-emerged as a potential fibrinolytic treatment 1,5,18) . Furthermore, a large number of studies have reported that UK thrombolysis following SICH both increases clot resolution rate and improves clinical outcome 2,3,7,18,20) .…”
Section: Introductionmentioning
confidence: 99%